LITERASI DIGITAL: PELUANG DAN TANTANGAN DALAM MEMBANGUN KARAKTER PESERTA DIDIK DIGITAL LITERACY: OPPORTUNITIES AND CHALLENGES IN BUILDING STUDENT CHARACTER - Fadlin Fajri; Mardianto Mardianto; Muhammad Irwan Padli Nasution (Intelegensia : Jurnal Pendidikan Islam, 2023)
In this day and age the use of technology has become very fast and massive, and today's technology users do not look at age and gender status with easy use. The purpose of writing articles is to present opportunities and challenges in building students' character in digital literacy. The research method is to use literature research using national and international journals, the results of the research include the challenges of spreading fake news, rampant negative content, triggering bullying in cyberspace, decreasing the moral quality of students, and the lack of technologically literate educators as well as opportunities for digital literacy in building character students namely supporting educational progress, eradicating illiteracy in students, supporting student skills and understanding digital responsibility as students. Based on the results of the research, the conclusion of the study is that digital literacy has positive and negative impacts for each individual, in schools, especially students, it is something that must be the responsibility of teachers and parents who are responsible for students at home and in the surrounding environment.